2015
DOI: 10.1039/c5ob01574j
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of α,β-unsaturated γ-butyrolactones and γ-butyrolactams via decarboxylative iodination of paraconic acids and β-carboxyl-γ-butyrolactams using 1,3-diiodo-5,5-dimethylhydantoin

Abstract: A convenient synthetic approach to α,β-unsaturated γ-butyrolactones and α,β-unsaturated γ-butyrolactams is developed. The reaction proceeds via decarboxylative iodination of paraconic acids and β-carboxyl-γ-butyrolactams, employing 1,3-diiodo-5,5-dimethylhydantoin (DIH) under irradiation, followed by dehydroiodination of β-iodo-γ-butyrolactones and γ-butyrolactams providing good yields of α,β-unsaturated γ-butyrolactones and γ-butyrolactams, which are synthetically useful building blocks in organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…For example, Spirofragilide is a sesquiterpene that is isolated from marine sponge Dysidea fraglis, possesses antitumor, anti-inflammatory, antibiotic, and anti-HIV activities. [15] Stypolactone is a diterpenoid isolated from brown alga, Stypodium zonalethat contains spirobutenolide as a sub-structure. [16] Two pigments, hydnuferruginin and hydnuferrugin [17] have been isolated from the sporophores of fungi Hydnellumferrugineum and H. zonatum.…”
Section: Important Natural Products Containing Spiro δ à Butenolides mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Spirofragilide is a sesquiterpene that is isolated from marine sponge Dysidea fraglis, possesses antitumor, anti-inflammatory, antibiotic, and anti-HIV activities. [15] Stypolactone is a diterpenoid isolated from brown alga, Stypodium zonalethat contains spirobutenolide as a sub-structure. [16] Two pigments, hydnuferruginin and hydnuferrugin [17] have been isolated from the sporophores of fungi Hydnellumferrugineum and H. zonatum.…”
Section: Important Natural Products Containing Spiro δ à Butenolides mentioning
confidence: 99%
“…The presence of Δ α , β ‐ and Δ β , γ ‐butenolides as subunits in different naturally occurring biologically active spirobutenolides are primarily responsible for pharmacological responses and have acquired unique place. For example, Spirofragilide is a sesquiterpene that is isolated from marine sponge Dysidea fraglis , possesses antitumor, anti‐inflammatory, antibiotic, and anti‐HIV activities . Stypolactone is a diterpenoid isolated from brown alga, Stypodium zonale that contains spirobutenolide as a sub‐structure .…”
Section: Important Natural Products Containing Spiro δ−Butenolides Anmentioning
confidence: 99%
“…Many different methods for their synthesis by de novo ring construction have been reported. Examples include cyclization of α,β-unsaturated γ-amino acids, [9] Mo-catalyzed reductive coupling of 1,2-diketones with α-ketoamides, [10] ring-closing metathesis of Nallylacrylamides, [11] radical ipso-cyclizations, [12] aminolysis of 2,5-dimethoxydihydrofuran, [13] dehydroiodination of 4-iodopyrrolidin-2-ones [14] and catalytic methods employing Pt, [15] Pd [16] and Fe. [17] Methods for transformation of pyrroles into Δ 3 -pyrrol-2-ones are less numerous, but approaches have been reported that rely on the reaction of a preexisting substituent at the pyrrole 2-position.…”
Section: Introductionmentioning
confidence: 99%
“… Phenylglyoxylic acid was also recently reported as an effective PS for the preparation of 3a – c benzyl esters in batch . Paraconic acids are synthetic or naturally occurring, and many of them are endowed with promising biological activities. , Compounds 3a – c are currently commercially available and are reported as building blocks for the preparation of biologically relevant molecules. , …”
Section: Introductionmentioning
confidence: 99%